Data-Driven Computational Intelligence for Scientific Programming - Rubio-Largo, Álvaro (2019)
Rubio-Largo, Á., Preciado, J. C., & Iribarne, L. (2019). Data-Driven Computational Intelligence for Scientific Programming. Scientific Programming,[5235706].[Editorial]. Doi: https://doi.org/10.1155/2019/5235706